The effect of thermocycling on the color stability of high translucency monolithic lithium disilicate and cubic zirconia materials - Maha Suliman Mezied (Wolters Kluwer Medknow Publications, 2022)
Introduction: The color stability and esthetic is an important factor of the long-term clinical success of dental ceramic restorations. However, the impact of thermocycling on the color stability of high translucency monolithic lithium disilicate and cubic zirconia materials is not well known. Aim: To evaluate the effect of thermocycling on the color stability of three types of monolithic cubic zirconia compared with one type of lithium disilicate. Materials and Methods: A Four groups of 10 disc-shaped specimens (10 mm x 1.2 mm) were made from: One brand of lithium disilicate (IPS e.max CAD® HT (E.max)) as a control, and three brands of cubic zirconia (Katana UTML, Cercon XT, and Ceramill Zolid FX UT) as experimental groups. Color analysis of specimens were performed before and after thermocycling by using a Spectrophotometer (Hunterlab, EasyMatch QC. Ver 4.90). Then, same discs were subjected to thermocycling for 10000 cycles. The data was analyzed with one-way ANOVA, Tukey's post hoc test. Data analyses were evaluated at a significance level of P < 0.05. Results and Discussion: Parameters L*, a*, and b* were statistically significant differences before and after AAA among groups (P<0.001). The IPS e.max CAD® HT showed the greatest change in color (ΔE= 2.15±0.24), followed by Cercon XT (ΔE= 1.70±0.22), Ceramill Zolid FX UT (ΔE= 1.44±0.25), and least change in color was Katana UTML (ΔE= 1.41±0.41). The Tukey's post hoc test, showed that the IPS e.max CAD® HT had significant changes when compared to the other materials (P<0.05). Conclusion: The effect of thermocycling on the color stability in this study results were significant effect in the (ΔE) of the four tested materials. The IPS e.max CAD® HT the greatest change in color and the and least change in color was Katana UTML. The color difference was significant within all groups, but changes were not a clinically perceivable.